2007
DOI: 10.1002/asna.200610734
|View full text |Cite
|
Sign up to set email alerts
|

Leakage of photospheric motions into the magnetic solar atmosphere: new prospects of magneto‐seismology

Abstract: The leakage and coupling of solar global oscillations to the overlaying magnetized solar atmosphere is investigated in this paper. Solar global acoustic oscillations may couple through resonant absorption to atmospheric local magnetic eigenoscillations (i) resulting in small shifts of the order of µHz in the real part of their frequencies as compared to their non-magnetic counterparts, and (ii) causing dissipation of wave energy and a consequent line broadening of the modes. Alternatively, global modes may als… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…Recently resonant absorption has acquired a new applicability when the observed damping of waves and oscillations in coronal loops has been attributed to resonant absorption. Hence, resonant absorption has become a fundamental constituent block of one of the newest branches of solar physics, called coronal seismology (see e.g., Nakariakov et al 1999;Ruderman & Roberts 2002;Goossens et al 2002;Arregui et al 2007;Ballai et al 2008;Goossens et al 2008;Terradas et al 2008) when applied to corona and solar magneto-seismology when applied to the en-tire coupled solar atmosphere (see e.g., Erdélyi et al 2007;Verth 2007;Verth et al 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Recently resonant absorption has acquired a new applicability when the observed damping of waves and oscillations in coronal loops has been attributed to resonant absorption. Hence, resonant absorption has become a fundamental constituent block of one of the newest branches of solar physics, called coronal seismology (see e.g., Nakariakov et al 1999;Ruderman & Roberts 2002;Goossens et al 2002;Arregui et al 2007;Ballai et al 2008;Goossens et al 2008;Terradas et al 2008) when applied to corona and solar magneto-seismology when applied to the en-tire coupled solar atmosphere (see e.g., Erdélyi et al 2007;Verth 2007;Verth et al 2007).…”
Section: Introductionmentioning
confidence: 99%
“…At statement of this task, we take into account the fact that the energy of the photospheric oscillations is transformed partly into the energy of Alfven waves that propagate upward and reach the solar corona. Then they are transported into the heliosphere over long distances by the solar wind (Erdélyi et al 2007;Tomczyk et al 2007;Mathioudakis et al 2013). According to Potapov et al (2012Potapov et al ( , 2013 the Alfven waves driven by the 5-minute solar oscillations are observed at the Earth's orbit.…”
Section: Introductionmentioning
confidence: 99%